Analytical and physical electrochemistry - Girault, Hubert H. (Marcel Dekker, 2004)
The study of electrochemistry is pertinent to a wide variety of fields, including bioenergetics, environmental sciences, and engineering sciences. In addition, electrochemistry plays a fundamental role in specific applications as diverse as the conversion and storage of energy and the sequencing of DNA. Intended both as a basic course for undergraduate students and as a reference work for graduates and researchers, Analytical and Physical Electrochemistry covers two fundamental aspects of electrochemistry: electrochemistry in solution and interfacial electrochemistry. By bringing these two subjects together into a single volume, the author clearly establishes the links between the physical foundation and the analytical applications of electrochemistry. The philosophy of Analytical and Physical Electrochemistry has been to publish all the mathematical derivations in detail, allowing you, if you so desire, to follow the calculations that lead to the main results. With this rigorous approach, the author has provided a book of reference constructed from first principles. In this respect, the nomenclature and standards of the IUPAC (International Union of Pure and Applied Chemistry) are observed.